2013
DOI: 10.1186/1472-6785-13-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding reveals diversity of Hymenoptera and the dominance of parasitoids in a sub-arctic environment

Abstract: BackgroundInsect diversity typically declines with increasing latitude, but previous studies have shown conflicting latitude-richness gradients for some hymenopteran parasitoids. However, historical estimates of insect diversity and species richness can be difficult to confirm or compare, because they may be based upon dissimilar methods. As a proxy for species identification, we used DNA barcoding to identify molecular operational taxonomic units (MOTUs) for 7870 Hymenoptera specimens collected near Churchill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 50 publications
3
61
0
2
Order By: Relevance
“…Indeed, in some cases where integrative taxonomic analyses that included DNA and morphological analyses were conducted coincidentally, it was found that barcodes alone would have recognized more than 97% of the species in the studies (Fernandez-Triana et al 2011). Furthermore, because the data are public such analyses are directly available to interested taxonomists in the future (Stahlhut et al 2013). …”
Section: Doubts About Anomalous Diversity Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, in some cases where integrative taxonomic analyses that included DNA and morphological analyses were conducted coincidentally, it was found that barcodes alone would have recognized more than 97% of the species in the studies (Fernandez-Triana et al 2011). Furthermore, because the data are public such analyses are directly available to interested taxonomists in the future (Stahlhut et al 2013). …”
Section: Doubts About Anomalous Diversity Patternsmentioning
confidence: 99%
“…Upon collection, all specimens were preserved in 95% ethanol for sorting and DNA extraction. Specimens for each locality were selected randomly from traps for barcoding as described in Stahlhut et al (2013). DNA was extracted and sequences generated using standard methods detailed elsewhere (Smith et al 2006(Smith et al , 2007(Smith et al , 2008.…”
Section: Data Collection and Molecular Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alaska, Manitoba, Nunavut, and Yukon Territory) and may reflect an increase in the availability of material recently collected in arctic and sub-arctic localities of North America (e.g., Fernández-Triana et al 2011;Stahlhut et al 2013). Other new records fill gaps in the known distribution of species.…”
Section: Resultsmentioning
confidence: 99%
“…For North America, and Canada in particular, several DNA barcoding projects have been undertaken for pollinators (e.g., Sheffield et al 2009;Hebert and Landry 2010;Hebert and Humble 2011;Zahiri et al 2014Zahiri et al , 2017, and many other taxa. These DNA barcode libraries can assist traditional morphological taxonomy by allowing identification of life stages for which keys are not available and/or taxonomy is more difficult (e.g., Slowik and Blagoev 2012), associating sexes (e.g., Sheffield et al 2011b), and in studies assessing biological diversity within regional (e.g., Sheffield et al 2009) and poorly studied habitatspecific biotas (e.g., Smith et al 2005Smith et al , 2009Stahlhut et al 2013). DNA barcode sequences (i.e., cytochrome c oxidase subunit I (COI)) and other genetic sequences themselves also contribute to molecular systematics; combining the DNA barcode gene with a single nuclear gene has proven useful for accurate, node-dated phylogenies for bees (Trunz et al 2016).…”
Section: Introductionmentioning
confidence: 99%